Perfil periodontal de pacientes portadores de alterações endócrino-metabólicas - Lima, Danilo Lopes Ferreira (2007)
Objective- Convinced that periodontium, many times, can show alterations in human health, the aim of these studies was to investigate the periodontal situation in patients with endocrine-metabolic disorders such as, Berardinelli-Seip Syndrome, hyperthyroidism, hypothyroidism and acromegaly. Methods- Eight patients with Berardinelli-Seip Syndrome, 16 acromegalics, 30 hypothyroids, 30 hyperthyroids, and a control group with 35 patients were evaluated. Clinical attachment loss, probing depth, gingival bleeding index, gingival overgrowth and Index of Decayed, Missing and Filled Teeth were measured in each patient. All ethical aspects were rigidly observed, being the study conducted after its approval by the University of Fortaleza Research Ethics Committee. Results- The presence of periodontitis was marked in hyperthyroids and in patients with Berardinelli-Seip Syndrome. Hypothyroids showed not much presence of periodontitis, while all acromegalics presented absence of periodontitis. Conclusions- The protective effect of periodontitis in acromegalic patients is a new finding, whose mechanisms are not yet clear, but may be related to the anabolic effects of growth hormone. The presence of periodontitis in Berardinelli-Seip Syndrome may occur due the early onset of diabetes. In hyperthyroids, the high prevalence of periodontitis could be linked to thyroid hormones effects on bone, explaining also the minor prevalence in hypothyroids